Some forms of the organization of interethnic communication in the modern megalopolis - Kosiborod, Olga; Rykunina, Natalia (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
The article is devoted to the preservation and development of the multicultural environment of the capital. The focus is on the analysis of the organization of public events for multinational voters of the city. Addresses the issues of history and current state of the festival movement in the city.This article discusses new forms of education programs, created in close cooperation with diasporas of Moscow. Analyzes the use of modern technology media and Internet space, to create a vast field of information capable of creating a high level of tolerance and interaction between people of different nationalities. (International festival «Moscow – city of peace held since 2002, Educational program «Moscow – city of peace» tested in secondary and higher educational institutions of Moscow since 2006, the project «Multicultural informational portal» has passed approbation in the public chamber of Russia and received the approval of interested organizations.) In the framework of this article is the draft of multicultural information portal (web portal project has been tested in the Public Chamber of Russia and received the approval of the concerned organizations). Materials provided in the article by these projects are author's developments of the authors of this article.